1991
DOI: 10.1149/1.2085793
|View full text |Cite
|
Sign up to set email alerts
|

The Equilibrium of the Chemisorption of TiCl4,  H 2, and  N 2 on Titanium Nitride

Abstract: For the purpose of clarifying the process of the CVD of normalTiN , the chemisorption of TiCl4 , H2 , and N2 on normalTiN has been investigated by the use of a thermal conductivity detector at 900 and 950 K. It has been found that the equilibrium constant of the chemisorption and the adsorption heat of TiCl4 molecules are larger than those of hydrogen atoms and nitrogen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1b) is located only 1.7 kcal/mol higher. A study of hydrogen chemisorption on TiN using a thermal conductivity detector at 900 and 950 K gave an adsorption energy of 60.3 kcal/mol [27]. The Ti-H bond length is more influenced by the relaxation of the surface and is reduced to [29].…”
Section: Adsorption and Diffusion Of Atomic Hydrogen On The Tin (100)mentioning
confidence: 99%
“…1b) is located only 1.7 kcal/mol higher. A study of hydrogen chemisorption on TiN using a thermal conductivity detector at 900 and 950 K gave an adsorption energy of 60.3 kcal/mol [27]. The Ti-H bond length is more influenced by the relaxation of the surface and is reduced to [29].…”
Section: Adsorption and Diffusion Of Atomic Hydrogen On The Tin (100)mentioning
confidence: 99%
“…38 In this study, the main adsorbed species are chloride, hydrogen, and nitrogen, etc. You et al 39 showed that the capability of adsorption of chloride is much stronger than hydrogen and nitrogen, and the adsorbed species are considered to tend to combine with Ti atoms more than with N atoms on the TiN surface. The ͑111͒ planes are the exchange layers of pure Ti and pure N, whereas the Ti layer is commonly the outest layer due to the lower surface energy.…”
Section: The Fastest Growth Orientation Of Crystalsmentioning
confidence: 99%
“…Cl.s + H.s ~-HCI(g) + 2s [30] N.s + H.s ~ s.NI-I + s [31] where s denotes an active site. The rds of this alternative reaction model is given by Eq.…”
Section: Ka = K12k~/2k~/2kskllmentioning
confidence: 99%